Effectiveness of Counseling Based on Functional Analytic Psychotherapy with Enhanced Cognitive Therapy on the Sexual Quality of Life of Married Adolescent Women - Gholami, Maryam; Ahmadi, Atefeh; Taebi, Mozhgan; Jahani, Yunes; Alidousti, Katayoun (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective Early marriage has many deleterious effects on the health of girls, such as sexual dissatisfaction, an inevitable result of the lack of sufficient knowledge about sexual issues at the time of the marriage. The goal of the present study was to determine the effectiveness of counseling based on functional analytic psychotherapy with enhanced cognitive therapy (FECT) on the sexual quality of life of married adolescent women.Methods This clinical trial was conducted between July and October 2019 on 150 married adolescent women who met the inclusion criteria. In the intervention group, FECT was conducted in sixteen 90-minute sessions twice a week. The Sexual Quality of Life-Female (SQOL-F) questionnaire was used. When the study ended, the control group was given the choice of receiving the same intervention as the intervention group.Results The paired t-test showed a significant difference between the mean score of sexual quality of life before (52.33 ± 23.09) and after (88.08 ± 10.51) counseling in the intervention group (p < 0.0001). According to the analysis of covariance, there was a significant difference between the score on sexual quality after counseling between the intervention (88.08 ± 10.51) and control (60.32 ± 23.73) groups (p < 0.0001). There was also a significant difference between the mean score on the four dimensions of sexual quality of life in the intervention group (p < 0.0001).Conclusion The results showed that counseling based on FECT improved the sexual quality of life in all dimensions in married adolescent women.
Keywords: functional analytical psychotherapy (FAP); cognitive behavioral therapy (CBT); sexual quality of life; married women; adolescents